2007
DOI: 10.1175/jam2454.1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Equations for the Stable Boundary Layer Height: Evaluation and Dimensional Analysis

Abstract: The performance of diagnostic equations for the stable boundary layer height h is evaluated with four observational datasets that represent a broad range of latitudes, land use, and surface roughness. In addition, large-eddy simulation results are used. Special care is given to data-quality selection. The diagnostic equations evaluated are so-called multilimit equations as derived by Zilitinkevich and coworkers in a number of papers. It appears that these equations show a serious negative bias, especially for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 62 publications
6
60
0
2
Order By: Relevance
“…At full scale, assuming a wind speed of, say, 10 m s -1 rather than the !1.5 m s -1 of these experiments, Eq. 9 gives this as equivalent to 4.9#10 -4 #20 K m -1 = 0.01 K m -1 , comparable to levels given, for example, by Mahrt et al (1979) and André and Mahrt (1982), and with more recent data given by Steeneveld et al (2007). …”
Section: Stable Boundary Layersupporting
confidence: 89%
“…At full scale, assuming a wind speed of, say, 10 m s -1 rather than the !1.5 m s -1 of these experiments, Eq. 9 gives this as equivalent to 4.9#10 -4 #20 K m -1 = 0.01 K m -1 , comparable to levels given, for example, by Mahrt et al (1979) and André and Mahrt (1982), and with more recent data given by Steeneveld et al (2007). …”
Section: Stable Boundary Layersupporting
confidence: 89%
“…The values found with the two methods range between 10 and 150 m; the correlation coefficient is 0.8. The Richardson number method generally gives lower values with respect to the visual observation method; the mean difference is 12 m. On the other hand, no correlation and a systematic overestimation were found between the stable layer height determined from experimental data and the values estimated using the parametrizations for the stable boundary layer given in Table 1 and the formulation proposed by Steenelveld et al (2007). A better correlation is obtained with the formulation proposed by Zilitinkevich (2002) for the LLSL.…”
Section: Discussionmentioning
confidence: 76%
“…The parametrizations summarized in Table 1 and the formulation proposed by Steenelveld et al (2007) show, however, a correlation with the height corresponding to the surface temperature inversion that does not necessarily correspond to the stable boundary-layer height.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, only the equilibrium BL top can be provided rather than the actual BL height (Zilitinkevich and Baklanov, 2002). The limits of the Richardsonnumber approach are further discussed by Vogelezang and Holtslag (1996) and Steeneveld et al (2007) and alternative approaches to predict the boundary layer are suggested.…”
Section: Bl Top From Cosmo Modelmentioning
confidence: 99%